Outcome of 1051 Octogenarian Patients With ST‐Segment Elevation Myocardial Infarction Treated With Primary Percutaneous Coronary Intervention: Observational Cohort From the London Heart Attack Group. Issue 6 (June 2016) - Bromage, Daniel I.; Jones, Daniel A.; Rathod, Krishnaraj S.; Grout, Claire; Iqbal, M. Bilal; Lim, Pitt; Jain, Ajay; Kalra, Sundeep S.; Crake, Tom; Astroulakis, Zoe; Ozkor, Mick; Rakhit, Roby D.; et al.
Abstract : Background: ST‐segment elevation myocardial infarction is increasingly common in octogenarians, and optimal management in this cohort is uncertain. This study aimed to describe the outcomes of octogenarians with ST‐segment elevation myocardial infarction treated by primary percutaneous coronary intervention. Methods and Results: We analyzed 10 249 consecutive patients with ST‐segment elevation myocardial infarction treated with primary percutaneous coronary intervention between 2005 and 2011 at 8 tertiary cardiac centers across London, United Kingdom. The primary end point was all‐cause mortality at a median follow‐up of 3 years. In total, 1051 patients (10.3%) were octogenarians, with an average age of 84.2 years, and the proportion increased over the study period ( P =0.04). In‐hospital mortality (7.7% vs 2.4%, P <0.0001) and long‐term mortality (51.6% vs 12.8%, P <0.0001) were increased in octogenarians compared with patients aged <80 years, and age was an independent predictor of mortality in a fully adjusted model (hazard ratio 1.07, 95% CI 1.07–1.09, P <0.0001). Time‐stratified analysis revealed an increasingly elderly and more complex cohort over time. Nonetheless, long‐term mortality rates among octogenarians remained static over time, and this may be attributable to improved percutaneous coronary intervention techniques, including significantly higher rates of radial access and lower bleeding complications. Variables associated with bleeding complications were similar between octogenarian and younger cohorts. Conclusions: In this large registry, octogenarians undergoing primary percutaneous coronary intervention had a higher rate of complications and mortality compared with a younger population. Over time, octogenarians undergoing primary percutaneous coronary intervention increased in number, age, and complexity. Nevertheless, in‐hospital outcomes were reasonable, and long‐term mortality rates were static.